THE EFFECT OF TOFU PULP WASTE BOKASHI ON GROWTH AND YIELD OF SNAPS IN ULTISOL SOIL - usman .; surachman .; astina . (Jurnal Sains Pertanian Equator, 2020)
This study aims to determine the effect of tofu pulp waste bokashi on the growth and yield of snaps and to determine how many tofu pulp waste bokashi the best to improve the growth and yield of snaps in ultisol soil. This study held from April 10st to June 10th 2019, the research was conducted in the experimental land of the faculty of agriculture at Tanjungpura University. The method used is Complete Randomized Design (CRD) of one factor. The treatment consisted of 5 treatments, namely (= tofu pulp waste bokashi 1 kg/polybag, = tofu pulp waste bokashi 2 kg/polybag, = tofu pulp waste bokashi 3 kg/polybag, = tofu pulp waste bokashi 4 kg/polybag, = tofu pulp waste bokashi 5 kg/polybag) all treatments were repeated 5 times, each treatment consisting of 4 plant samples. The results showed that the application of 5 kg/polybag  tofu pulp waste bokashi was the best of improve the growth and yield of snaps in ultisol soil. Key Word: PMK soil, snaps, tofu pulp waste bokashi.